Respuesta :

Answer:1,2,3

Step-by-step explanation:

F(x)=[tex]x^{3}[/tex]+2[tex]x^2[/tex]-[tex]5x[/tex]-[tex]6[/tex]=0

disintegrating 2[tex]x^2[/tex] to [tex] x^2[/tex] + [tex]x^2[/tex]

[tex]x^{3}[/tex]+[tex]x^2[/tex]+[tex]x^2[/tex]-[tex]5x-6[/tex]=0

[tex]x^2[/tex][tex]\left ( x+1\right )[/tex]+[tex]x^2[/tex]-5x-6=0

[tex]x^2[/tex][tex]\left ( x+1\right )[/tex]+[tex]x^2[/tex]-6x+x-6=0

[tex]x^2[/tex][tex]\left ( x+1\right )[/tex]+[tex]\left (x-6 \right )[/tex][tex]\left ( x+1\right )[/tex]=0

[tex]\left ( x+1\right )[/tex][tex]\left ( x^2+x-6\right )[/tex]=0

[tex]\left ( x+1\right )[/tex][tex]\left ( x^2+3x-2x-6\right )[/tex]=0

[tex]\left ( x+1\right )[/tex][tex]\left ( x+3\right )[/tex][tex]\left ( x-2\right )[/tex]=0

ACCESS MORE